Comparison of factor scores and factor structures of NEO-PI R between job applicants and normative group - Jung, SungCheol (Korean Journal of Industrial and Organizational Psychology, 2011)
The present study aimed to analyse the extent to which Positive Presentation Management influences on factor scores and factor structure of NEO-PI R personality inventory in the context of personnel selection. Subjects of present study are 21,349 applicants who applied for a French public transport organization and filled out NEO-PI R personality inventory during 5 years. Comparisons with French norm showed significant differences in scores of all of five factors: scores of Neuroticism and Openness are lower than French norm (deflation of factor scores) and those of Extraversion, Agreeableness, and Conscientiousness are higher than French norm (inflation of factor scores). Confirmatory factor analysis and Procrustes rotation demonstrated that variations of factor scores due to Positive Presentation Management did not affect 5-dimensional factor structure. From these results, we can conclude that applicants’ Positive Presentation Management affect factor scores but does not affect structural validity of NEO-PI R. We further proposed a norm of NEO-PI R scores for individuals in contexts of high-stakes testing.